2024
DOI: 10.3346/jkms.2024.39.e7
|View full text |Cite
|
Sign up to set email alerts
|

Digital Health Technology Use Among Older Adults: Exploring the Impact of Frailty on Utilization, Purpose, and Satisfaction in Korea

Hyejin Lee,
Jung-Yeon Choi,
Sun-wook Kim
et al.

Abstract: Background The importance of digital technology is increasing among older adults. In this study, the digital health technology utilization status, purpose, and satisfaction of older adults were investigated according to frailty. Methods A face-to-face survey was conducted among adults aged 65 years or older. Frailty was defined using the Korean version of the fatigue, resistance, ambulation, illnesses, and loss of weight scale. Results A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In this study, telephone and e-mail were used as examples of indirect contact, with cell phones and smartphones often serving as tools for these communications. However, a previous study showed that while 80% of older adults use smartphones, usage of specific services like e-mail and messenger varies greatly, suggesting individual differences in proficiency [ 25 ]. This means that while those with high proficiency could leverage smartphones for indirect interaction, those with low proficiency may have struggled, potentially affecting our study results.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, telephone and e-mail were used as examples of indirect contact, with cell phones and smartphones often serving as tools for these communications. However, a previous study showed that while 80% of older adults use smartphones, usage of specific services like e-mail and messenger varies greatly, suggesting individual differences in proficiency [ 25 ]. This means that while those with high proficiency could leverage smartphones for indirect interaction, those with low proficiency may have struggled, potentially affecting our study results.…”
Section: Discussionmentioning
confidence: 99%